New men : reconstructing the image of the veteran in late nineteenth-century American literature and culture - Casey, John A., Jr (Reconstructing America (Series), 2015)
"New Men uncovers the narrative of veteran reentry into civilian life and exposes a growing gap between how former soldiers of the Civil War saw themselves and the representations of them created by late nineteenth-century American society. This gap generated a new conception of the "veteran" still influential today"--